Dye adsorbent by pineapple parts activated carbon - Nagendran Selvanathan (2015)
Dyes are used extensively in many industries making the research on color production more important. Despite that, dyes are important class of pollutant in which it is disposed in water resources and causes major environmental problems due to toxicity and carcinogenic property of dye. However, the disposed dye into the environment can be treated by several alternatives. In this study, activated carbon derived from different pineapple waste namely pineapple crown, core and peel were prepared by chemical activation using phosphoric acid (H₃PO₄) and sodium hydroxide (NaOH). Laboratory prepared activated carbons were used to identify the suitability of different pineapple waste activated carbon to adsorb methylene blue and malachite green dyes. The results obtained were compared in terms of percentage of adsorption and percentage of color removal (ADMI). The results indicated that the activated carbon derived from pineapple crown shows maximum adsorption of methylene blue (99.48%) and malachite green (98.94%). This research was also used to determine the appropriate activation method between acid (H₃PO₄) and base activation (NaOH) by comparing the percentage of adsorption by both activation methods. Results obtained shows that the acid activated carbon serves as the best activated carbon with highest adsorption value of 99.48%. This study shows a benefit of transforming agriculture waste to value added product and also helps to solve over abundance pineapple waste problem.